Persistent effects of early-life exposure to dibutyl phthalate on zebrafish: Immune system dysfunction via HPA axis - Yue Tao; Yanyan Gu; Haorui Wang; Guanyu Zhong; Aoxue Wang; Jianhua Qu; Jiayi Feng; Ying Zhang (Environment International)
The plasticizer dibutyl phthalate (DBP) is one of the common contaminants in the aquatic environment and has been verified to be detrimental to aquatic organisms. In this research, zebrafish was employed to explore the toxic mechanism of DBP at environmental concentrations. The findings indicated that DBP led to abnormal development of zebrafish larvae, encompassing an increase in heart rate and malformation rate, as well as a reduction in survival rate and hatching rate. DBP also induced HPA axis activation, increased glucocorticoid content and microglia activation in zebrafish larvae. Moreover, adult zebrafish in the early-life exposure and long-term exposure groups demonstrated anxiety-like and depression-like behaviors. RNA-seq analysis revealed that early embryonic exposure to DBP led to persistent damage in zebrafish that could not be recovered in adulthood. The HPA axis was more severely disorganized in males than in females, and sex-specific differences were also shown in immunotoxicity. It is speculated that the immune system disorder could partially attribute to the out-of-control HPA axis, while the activation of inflammatory cells and inflammatory factors will further exacerbate the situation of HPA axis dysregulation.